The source and pathophysiologic significance of excreted cadmium - Soisungwan Satarug (2020)
© 2019 by the authors. In theory, the identification of the source of excreted cadmium (Cd) might elucidate the pathogenesis of Cd-induced chronic kidney disease (CKD). With that possibility in mind, we studied Thai subjects with low, moderate, and high Cd exposure. We measured urine concentrations of Cd, ([Cd]u); N-acetyl-β-D-glucosaminidase, a marker of cellular damage ([NAG]u); and β2-microglobulin, an indicator of reabsorptive dysfunction ([β2MG]u). To relate excretion rates of these substances to existing nephron mass, we normalized the rates to creatinine clearance, an approximation of the glomerular filtration rate (GFR) (ECd/Ccr, ENAG/Ccr, and Eβ2MG/Ccr). To link the loss of intact nephrons to Cd-induced tubular injury, we examined linear and quadratic regressions of estimated GFR (eGFR) on ECd/Ccr, eGFR on ENAG/Ccr, and ENAG/Ccr on ECd/Ccr. Estimated GFR varied inversely with both ratios, and ENAG/Ccr varied directly with ECd/Ccr. Linear and quadratic regressions of Eβ2MG/Ccr on ECd/Ccr and ENAG/Ccr were significant in moderate and high Cd-exposure groups. The association of ENAG/Ccr with ECd/Ccr implies that both ratios depicted cellular damage per surviving nephron. Consequently, we infer that excreted Cd emanated from injured tubular cells, and we attribute the reduction of eGFR to the injury. We suggest that ECd/Ccr, ENAG/Ccr, and eGFR were associated with one another because each parameter was determined by the tubular burden of Cd.